HUMAN CAPITAL OF POLISH NON-GOVERNMENTAL ORGANISATIONS: FROM MACROECONOMIC CONTEXT TO MICROECONOMIC IMPLICATIONS - Dyczkowski, Tomasz (Ekonomika, 2013)
Abstract. The paper1 aims at emphasizing the importance of a proper recognition and disclosure of human capital in non-governmental organizations (NGOs) on the example of Poland. Although NGOs do significantly contribute to social well-being, the economic focus paid to commercial businesses and public institutions causes that a scope of civil initiatives is not recognised to a sufficient extent. It is, therefore, a role of the Third Sector to promote its activities and to inform extensively on the effects generated. The issue which requires particular attention in this respect is the human capital which propels all benevolent activities.The author analyses, firstly, the historic, economic, and legal circumstances that shaped the modern Third Sector in Poland. Subsequently, an analysis of human resources available to Polish NGOs in comparison to the situation of their German and British counterparts is conducted. The results of a study on the attractiveness of the non-governmental sector as an employer are discussed next. The paper is concluded with a presentation of methods which enable to quantify and valuate human capital in a non-commercial environment, including the ratios used to monitor the development of that capital.The results presented in the paper clearly demonstrate that it was possible due to involvement of socially sensitive people to rebuild social activities in Poland after the long period of the state’s exclusivity in defining and addressing social issues. Those people made the initial human resources of Polish NGOs as their members, governors or volunteers. Nonetheless, the development of a comprehensive legal framework stimulating co-operation between the state and NGOs, and an extensive use of European funds helped to extend the labour force of the sector by 120 000 employees. A priority for now proves to be sustaining that growth by attracting young people. The results of the author’s study on the perception of the Third Sector by students show that most of them still know NGOs from mass media only, and one third of them would not consider working for an NGO in future. On the other hand, opinions of those who already work in a non-commercial environment prove to be positive, what entitles to formulate the conclusion that a better knowledge of the ways NGOs work is vital to build their human capital. If social managers develop proper systems of measuring and reporting human capital, such as the one presented in the paper, they will gain a tool to demonstrate that human capital of their organisations is used to make social initiatives as effective and efficient as possible.Key words: non-governmental organisation (NGO), the Third Sector, human resources, human capital